Calling a Thing What It Is: A Lutheran Approach to Whiteness. (March 2014) - Thompson, Deanna A.
Abstract The July 2013 acquittal of George Zimmerman in killing of African American teenager Trayvon Martin and the aftermath demonstrated that America is not yet cured from "the cancer of whiteness" that infects the heart of American Christianity. This article interrogates "whiteness" as a pressing American and religious issue. It looks to Martin Luther's theology of the cross as a way to both expose the sinfulness of whiteness and to offer a framework for dislodging it.